(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
A new family of biodegradable and functional amino acid-based poly(ester amide)s (AA-PEAs) have been designed and synthesized as a new generation of biodegradable biomaterials for biomedical applications. This paper provides an overview of this new generation of biodegradable biomaterials, their design strategy, synthesis, characterization, unique biological property and eventual biomedical applications. AA-PEAs are synthesized from 3 basic building blocks: amino acids, fatty diols and fatty diacids. Due to the enormous variety of these 3 building blocks, a wide range of AA-PEAs could be tailor-designed for meeting specific clinical needs. These AA-PEAs have been engineered into a variety of physical forms ranging from 3D microporous hydrogels, melt-spun fibers, electrospun fibrous membranes, films and microspheres. All these AA-PEAs have shown 2 unique biological properties: support natural wound healing, and muted inflammatory response.